EXPERIMENTAL PARTITION OF NICKEL BETWEEN MAGNETITE AND PYRRHOTITE - Medvedev A.Y.; Al'mukhamedov A.I. (My University, 1987)
Analysis of the very limited available information on natural parageneses shows that magnetite associated with sulfide ore is low in titanium, as well as in vanadium, relative to the accessory ores. The nickel content of such magnetite, conversely, is comparatively high. Its sizable scatter most likely is due to the presence of sulfide microinclusions in magnetite. These cannot be removed by traditional phase-separating techniques. To confirm the above-postulated trends, the authors have experimentally studied the nickel partition between magnetite and pyrrhotite over a wide temperature range under conditions of phase crystallization from a sulfide-oxide melt. The tests were run in evacuated quartz ampoules (Fa-Mt-Q buffer), where any residual oxygen was removed by burning metallic magnesium in the already sealed ampoule. The partition of nickel between phases was evaluated from data of emission spectroscopy because this element could not be directly determined by microprobe analysis in each phase on account of its low content and the subgraphic intergrowth of magnetite and pyrrhotite. Study results are discussed.